Efforts to prevent conflict and violence in educational institutions - Candramukti, Febrihada Gahas (Journal Intellectual Sufism Research (JISR), 2019)
Every educational institution would want a conducive and peaceful atmosphere in theschool environment within the scope of teaching and learning. This does not only apply to certainlevels, but almost at various levels of elementary, junior high school, high school and the like. But inthe school environment there is still intense conflict and violence, there are several types of conflictand violence in the educational environment which are examined using qualitative descriptive typeswith the theory of conflict and violence approach, including: Types without conflict, open conflict,surface conflict and conflict. The components of violence are structural violence and culturalviolence. Preventive action that should be done is first to socialize the type of punishment for theperpetrators of violence, secondly to design or implement a polite school system.